A de novo KCNQ2 Gene Mutation Associated With Non-familial Early Onset Seizures: Case Report and Revision of Literature Data - Gianluigi Laccetta; Simona Fiori; Matteo Giampietri; Annarita Ferrari; Valentina Cetica; Manuela Bernardini; Francesca Chesi; Sara Mazzotti; Elena Parrini; Massimiliano Ciantelli; Andrea Guzzetta; Andrea Guzzetta; et al. (Frontiers Media S.A., 2019)
Among neonatal epileptic syndromes, benign familial neonatal seizures (BFNS) are often due to autosomal-dominant mutations of the KCNQ2 gene. Seizures are usually characterized by asymmetric tonic posturing with apnea with onset in the first 7 days of life; they may even occur more than 10 times per day or evolve into status epilepticus. The delivery course of our patient was uneventful and family history was negative; on the second day of life the baby became pale, rigid, and apnoic during breastfeeding and appeared jittery and irritable when stimulated or examined. At age 3 days, she experienced clusters of generalized tonic seizures with pallor, desaturation, bradycardia, and partial response to intravenous phenobarbital; during her 4th and 5th days of life, three episodes of tonic seizures were noticed. At age 6 days, the patient experienced about 10 episodes of tonic seizures involving both sides of the body, which gradually responded to intravenous phenytoin. Electroencephalograms revealed abnormalities but brain MRI was normal. The patient is seizure-free since postnatal day 21; she is now 12 months old with cognitive development within normal limits at Bayley III Scale and mild motor delay. The patient is on maintenance therapy with phenobarbital since she was 7 months old. A de novo heterozygous mutation (c.853C>T/p.P285S) in the KCNQ2 gene was identified. We therefore describe a case of de novo KCNQ2-related neonatal convulsions with necessity of multiple anticonvulsants for the control of seizures, mutation occurring in the pore channel of the voltage-gated potassium channel subfamily Q member 2 associated with a likely benign course; furthermore, the same mutation of the KCNQ2 gene and a similar one (c.854C>A/p.P285H) have already been described in association with Ohtahara syndrome. Probably acquired environmental, perinatal and genetic risk factors are very important in determining the different phenotype; we hope that the rapid progress of analysis tools in molecular diagnosis can also be used in the search of an individualized therapeutic approach for these patients.